2017
DOI: 10.1016/j.ajog.2017.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Continuation of copper and levonorgestrel intrauterine devices: a retrospective cohort study

Abstract: Background Studies conflict on whether the duration of use of the copper intrauterine device is longer than that of the levonorgestrel intra-uterine device, and whether women who continue using intrauterine devices differ from those who discontinue. Objective We sought to assess continuation rates and performance of levonorgestrel intrauterine devices compared with copper intrauterine devices over a 5-year period. Study Design We performed a retrospective cohort study of 1164 individuals who underwent intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…Philips et al found that among IUD users, 49.3% had an education level above college, while 2.8% had a below high school education level. The study also suggested that education was not associated with early discontinuation of an IUD [6]. When assessing correlations between abortion, education, and all LARCs; Steinauer et al found 69.2% of participants who chose to use LARCs following aspiration abortion had high-school level of education or higher [8].…”
Section: Methodsmentioning
confidence: 92%
See 4 more Smart Citations
“…Philips et al found that among IUD users, 49.3% had an education level above college, while 2.8% had a below high school education level. The study also suggested that education was not associated with early discontinuation of an IUD [6]. When assessing correlations between abortion, education, and all LARCs; Steinauer et al found 69.2% of participants who chose to use LARCs following aspiration abortion had high-school level of education or higher [8].…”
Section: Methodsmentioning
confidence: 92%
“…Of copper IUD users, younger women had higher discontinuation rates, but the levonorgestrel IUD users' discontinuation rates were the same across all age groups [9]. Similarly, Phillips et al found that copper IUDs were more frequently discontinued by their younger users, but younger women were more likely to discontinue their levonorgestrel IUDs, although less so than young women with copper IUDs [6]. Two articles found that younger women were not any more likely to expel their IUDs than older women [5] [6].…”
Section: Methodsmentioning
confidence: 96%
See 3 more Smart Citations